Activity of sorghum aphid and its natural enemies in the context of agroecological and weather conditions - Koralewski, Tomasz E.; Brewer, Michael J.; Deleon, Leonel L.; Elliott, Norman C.; Giles, Kristopher; Szczepaniec, Adrianna; Faris, Ashleigh M. (Frontiers in Insect Science, 2025)
Agroecological-oriented areawide pest management leverages the innate ability of agroecosystem to suppress pests, and thus to utilize ecosystem services, a key component of sustainable agriculture. A growing body of knowledge on interactions between pests and their natural enemies allows us to recognize the complexity of these interactions that often depend on environmental circumstances. Sorghum aphid, Melanaphis sorghi (Theobald) (Hemiptera: Aphididae), is a recent but established pest of sorghum in the Great Plains of North America. Both predators and parasitoids prey on sorghum aphid but their activity and impact change throughout the area and throughout the year. Both landscape and weather factors have been shown to affect the abundance and numerical responses of these insects, consistent with observations in other aphid species. In this study we used data on counts of sorghum aphids, lady beetles (Coleoptera: Coccinellidae), and parasitoid wasps Aphelinus nigritus Howard (Hymenoptera: Aphelinidae) and Lysiphlebus testaceipes (Cresson) (Hymenoptera: Braconidae) collected in Kansas, Oklahoma and Texas states of the United States. We analyzed insect dynamics in the context of landscape and weather factors. We built multiple regression models using data from the years 2017–2019 for metrics such as maximum number of insects per leaf, response time of natural enemies to pest presence, and speed of increase in insect abundance. Our results indicate that various aspects of landscape composition, landscape configuration, and weather affect various insect groups and various aspects of insect dynamics in the field. Moreover, characteristics of specific landscape categories seemed to be more informative than overall measure of landscape diversity. Our study provides insights on interactions along both spatial and temporal scales, with the latter considered understudied.